Coping with catastrophes: A study of crop insurances from the perspective of small farmers in India - Zevenbergen, H (Utrecht University, 2014)
Small farmers are one of the hardest hit groups in the world that is affected by the negative consequences of a changing climate. Their absolute dependence on weather conditions makes them extremely vulnerable. A catastrophe can be as small as rains arriving too soon or too late in the season; destroying a harvest and trapping farmers into poverty. Over the last two decades, micro insurances have become more popular as risk management instrument and are offered to marginalised communities to build resilience at relatively affordable rates. Successful implementation of agricultural micro insurances throughout the world is still limited however. The country with the most experience, and that has even included these insurances in national policies, is India. With over three quarters of its farming population cultivating on less than 2 hectares of land (and thus falling in the category of small farmers) and being home to a wide range of climatic risks and conditions, this country is incredibly interesting and relevant to study regarding risk management for climate change in general and crop insurance in particular. However, crop insurances in India also face several challenges (such as basis risk, delays in payments and lack of awareness among farmers). Therefore, the following research question is central to this study: How can current crop insurances in India be improved to better suit the needs and wishes of small farmers?